Strategic decisions between short-term profit and sustainability - Philipp Haessler (Administrative Sciences, 2020)
Sustainability has evolved into one of the key topics for organizations and organizational researchers alike. To meet changing societal demands, organizations have to adapt their long-term strategies and incorporate environmental and social aspects into their product offerings and decision-making. However, at the same time companies must satisfy short-term profitability interests and demands from shareholders. An organization's sustainability commitment, strategy, or view is impacted by several influential factors, e.g., by the top management commitment or stakeholder integration. These factors have largely been studied individually without linking them. As such, the following study aims at creating a holistic view and framework for organizational influences and on sustainability. The framework is validated by a comparison to industrial practice in interviews with sustainability managers from the chemical and automobile industry, which are both highly relevant in the context of sustainability. Interview results suggest that the identified influential factors attributed to the four framework layers organization, top management, project team and project are relevant for industrial representatives. The view on and impact of specific influential factors can vary between companies and industries. The study further gives insights into the actual status and future direction of the management of corporate sustainability (CS) in practice.
Keywords: 350; automotive industry; chemical industry; corporate sustainability; corporate sustainability performance; decision-making; influential factors; trade-offs